Evidence-based guidelines for the management of abnormally invasive placenta: recommendations from the International Society for Abnormally Invasive Placenta - Collins, Sally L; Alemdar, Bahrin; van Beekhuizen, Heleen J; Bertholdt, Charline; Braun, Thorsten; Calda, Pavel; Delorme, Pierre; Duvekot, Johannes J; Gronbeck, Lene; Kayem, Gilles; Langhoff-Roos, Jens; Marcellin, Louis; et al. (American journal of obstetrics and gynecology, 2019)
The worldwide incidence of abnormally invasive placenta is rapidly rising, following the trend of increasing cesarean delivery. It is a heterogeneous condition and has a high maternal morbidity and mortality rate, presenting specific intrapartum challenges. Its rarity makes developing individual expertise difficult for the majority of clinicians. The International Society for Abnormally Invasive Placenta aims to improve clinicians' understanding and skills in managing this difficult condition. By pooling knowledge, experience, and expertise gained within a variety of different healthcare systems, the Society seeks to improve the outcomes for women with abnormally invasive placenta globally. The recommendations presented herewith were reached using a modified Delphi technique and are based on the best available evidence. The evidence base for each is presented using a formal grading system. The topics chosen address the most pertinent questions regarding intrapartum management of abnormally invasive placenta with respect to clinically relevant outcomes, including the following: definition of a center of excellence; requirement for antenatal hospitalization; antenatal optimization of hemoglobin; gestational age for delivery; antenatal corticosteroid administration; use of preoperative cystoscopy, ureteric stents, and prophylactic pelvic arterial balloon catheters; maternal position for surgery; type of skin incision; position of the uterine incision; use of interoperative ultrasound; prophylactic administration of oxytocin; optimal method for intraoperative diagnosis; use of expectant management; adjuvant therapies for expectant management; use of local surgical resection; type of hysterectomy; use of delayed hysterectomy; intraoperative measures to treat life-threatening hemorrhage; and fertility after conservative management.
Keywords: hysterektomie; abnormally invasive placenta; increta; Watchful Waiting; morbidly adherent placenta; Postpartum Hemorrhage; delfská metoda; poporodní krvácení; Placenta Accreta; guideline; management nemoci; gestační stáří; placenta accreta spectrum; hormony kůry nadledvin; hospitalizace; Gestational Age; Pregnancy; těhotenství; Oxytocics; Disease Management; Stents; Patient Positioning; Ureter; Cesarean Section; Oxytocin; accreta; konzervativní terapie; placenta; Delphi Technique; lidé; Hysterectomy; ženské pohlaví; placenta accreta; Humans; Hospitalization; ureter; stenty; percreta; polohování pacienta; Adrenal Cortex Hormones; Conservative Treatment; Female; pozorné vyčkávání; císařský řez; oxytocin; uterotonika